The Ryan Report in Ireland: before and after - Noel Howard (Scottish Journal of Residential Child Care)
The Commission to Inquire into Child Abuse (Government of Ireland, 2009) is the official name given to what we now know as the Ryan Report. It is so called because Sean Ryan, a justice of the Irish High Court took over from Justice Mary Laffoy in September 2003 to complete the work begun by her. The Ryan Report is about children, church and state. As for church and state the report shows how those two unquestioned pillars of Irish society criminally neglected the poorest and most vulnerable children and failed in their duty of care.